Association of carotid artery geometries with middle cerebral artery atherosclerosis. (July 2022) - Liu, Yi-Tong; Zhang, Zong-Mu-Yu; Li, Ming-Li; Gao, Shan; Feng, Feng; Xu, Wei-Hai
Abstract: Background and aims: Evidence shows that artery geometries play a role in atherogenesis by influencing blood flow dynamics. However, whether upstream artery geometries influence downstream atherosclerosis remains unclear. We aimed to investigate whether carotid artery geometries were associated with middle cerebral artery (MCA) atherosclerosis. Methods: We reviewed our institutional database of 3-dimensional head-neck combined high-resolution magnetic resonance imaging. The carotid artery geometries, carotid atherosclerosis, MCA configurations, and MCA atherosclerosis were examined. The associations between carotid artery geometry and MCA atherosclerosis were also analyzed. A final model integrating carotid artery geometries was established, and the incremental diagnostic value was evaluated and compared to a basic model that included only traditional risk factors. Results: Among the 575 artery units of the ipsilateral carotid artery and MCA, the artery units with MCA plaques (n = 273) were associated with a larger bifurcation angle (odds ratio [OR], 1.138 per 10-degree increase; 95% confidential interval [CI], 1.023–1.264) and kinking-type extracranial internal carotid artery (ICA; OR, 2.193; 95%CI, 1.283–3.748) compared with those without MCA plaques (n = 302). These associations were independent of traditional risk factors, carotid atherosclerosis, and MCA configuration. A larger carotid bifurcation angle was also associated with tandem ICA and MCA atherosclerosis (OR, 1.211 per 10-degree increase; 95%CI, 1.110–1.321). The incremental diagnostic value of carotid artery geometry to traditional risk factors was revealed by comparing the area under the curves of the two diagnostic models (basic model, 0.673 vs. final model, 0.701; p  = 0.016). Conclusions: Carotid artery geometries are independently associated with ipsilateral MCA atherosclerosis, providing new insights into the pathophysiology of intracranial atherosclerosis. Graphical abstract: Image 1 Highlights: A larger carotid bifurcation angle is associated with middle cerebral artery (MCA) atherosclerosis. The kinking-type extracranial internal carotid artery (ICA) is associated with MCA atherosclerosis. A larger carotid bifurcation angle is also associated with tandem atherosclerosis.